Molecular isotopic insights into hydrodynamic controls on fluvial suspended particulate organic matter transport. (1st October 2019) - Yu, Meng; Eglinton, Timothy I.; Haghipour, Negar; Montluçon, Daniel B.; Wacker, Lukas; Wang, Zicheng; Jin, Gui'e; Zhao, Meixun
Abstract: Hydrodynamic sorting has been shown to strongly influence the composition and age of organic carbon (OC) during sediment transport and burial in the marine environment, yet sorting effects on terrestrial OC (OCterr ) in fluvial systems remain poorly understood. We conducted size fractionation of suspended particle samples from the lower Yellow River, China, and examined variations in mass distribution and carbon isotopic (δ 13 C and Δ 14 C) composition of bulk OC and specific biomarkers among grain size fractions in order to investigate the influence of hydrodynamic sorting and selective transport on organic matter export. In general, the 16–32 μm and 32–63 μm fractions contributed the most of sediment mass while the majority of the OC resided in the 16–32 μm fraction. Over 80% of OC and n -fatty acids (FAs) were concentrated in <32 μm fractions. Significant differences in OC%, surface area (SA), Δ 14 COC, n -FAs contents, and compound-specific 13 C and 14 C compositions were found among size fractions. Of particular note was a progressive decrease of Δ 14 C values (i.e., increase in 14 C age) of long-chain (C26+28+30 ) FAs with decreasing grain size. Taken together, the bulk and molecular characteristics imply two distinct types of selective OCterr transport in the Yellow River. Coarser particles (>32 μm), characterized by relatively low SA, OC%, and Δ 14 COC values, but higher Δ 14 C values of C26+28+30 FAs, are inferred to reflect a combination of bedrock-derived detrital sediment and fresh vascular-plant material (e.g., plant fragments). In contrast, finer particles (<32 μm), exhibiting higher SA, OC%, and lower Δ 14 C26+28+30FAs values, reflect preferential transport of pre-aged, mineral soil-derived OC that is susceptible to repeated mobilization, as well as widespread dispersal in marginal seas. The latter, once buried in marine sediments, could account for the high burial efficiency of OCterr in the adjacent Bohai Sea and Yellow Sea. Thus, hydrodynamic sorting processes induce heterogeneity of composition and selective transport of OC. Bulk and molecular 14 C measurements of size-fractionated particles facilitate both elucidation of these processes and assessment of their impact on OC cycling in (and export from) rivers.